Study on the Long-Term Performance and Efficiency of Single-Well Circulation Coupled Groundwater Heat Pump System Based on Field Test - Zhu, Ke; Zeng, Yifan; Wu, Qiang; Xu, Shengheng; Tu, Kun; Liu, Xiaoxiu (Frontiers in Earth Science, 2021)
Although buildings are often heated and cooled by single-well circulation coupled groundwater heat pump systems. few studies have evaluated the long-term performance of these systems. Therefore, the present study investigates the performance of these systems by analyzing the efficiency and energy consumption based on four years of operating data. The results indicate that the coefficient of performance (COP) of a system gradually decreases because of thermal breakthrough or an accumulation of cold. In addition, the sealing clapboards could effectively slow down thermal breakthrough. In addition, compared with the heating period, the COP of the heat pump unit (HPU) and system increases, and the energy consumption decreases in the cooling period. It is also found that partial heat loss occurs when water from the single-well circulation outlet penetrates the main pipeline. Moreover, the heat exchange efficiency of a single HPU exceeds that of multiple HPU, and the COP of an HPU decreases during operation with increasing indoor temperature. Accordingly, we improve the COP by increasing the underground heat storage. We focus on optimizing the system design during long-term operation, which includes taking steps such as lengthening the sealing clapboards, using insulated pipe, discharging the remaining water, and adding intelligent control devices.